The Analysis of Skopos, Translation Methods and Strategies in BBC Online Articles of Middle East News - Robi Rizkiana (Passage, 2016)
The research aims to investigate and identify the skopos of the target texts, translation method and strategies used by BBC in translating Middle East news online articles. This research employed descriptive qualitative methodology with descriptive statistics method. The data were taken from BBC main web site for 20 original articles (English version) and BBC Indonesia for 20 translated articles (Indonesian version). The data were analyzed based on translation theories of translation methods proposed by Newmark (1988) and translation strategies, including selected microstrategies proposed by Schjoldager (2008, in Jensen, 2009); and strategies related to journalistic translation from Klaudy and Laviosa in Vybíralová (2012), Bani (2006), and Bielsa and Bassnett (2009). The result revealed that the skopos of the target texts is to make informative text in form of brief online news articles for Indonesian readers. The target texts also should have the characteristics of the journalistic translation which are to give less-effort readability (Bani, 2006) and immediate comprehension. The translation method which becomes the translator’s overall plan is Communicative Translation in 14 articles (70%) with 93 occurrences (50%). Communicative Translation makes the target texts comprehensive and acceptable to the readership (Newmark, 1988). It also establishes less-effort readability. The other methods are Faithful Translation in 6 articles (30%) with 72 occurrences (38%) and Free Translation with only 21 occurrences (11%). In translation strategies analysis, Explicitation has 28 occurrences (37%), Calque with 26 occurrences (34%), Change of sentence order with 10 occurrences (13%), Simplification with 9 occurrences (12%), Direct transfer with 2 occurrences (3%) and Inclusion of explanation with 1 occurrence (1%). Explicitation is used more often than calque in the translation process as one of the functional characteristics of informative text type which is to transmit referential contents (Reiss, 1976 in Munday, 2001). The other strategies, Cutting was used in 18 articles (90%) and there are 13 articles (65%) in which their titles were changed. 12 articles were changed from direct to indirect titles and one article from indirect to direct titles. Cutting supports the skopos by omitting additional information (subsections), while Indirect Titles make the target text titles brief and establish attraction to the target readers by presenting hint.